Brain Hypoxia Secondary to Diffusion Limitation in Hypoxic Ischemic Brain Injury Postcardiac Arrest. Issue 3 (March 2020) - Sekhon, Mypinder S.; Ainslie, Philip N.; Menon, David K.; Thiara, Sharanjit S.; Cardim, Danilo; Gupta, Arun K.; Hoiland, Ryan Leo; Gooderham, Peter; Griesdale, Donald E.
Abstract : Objectives: We sought to characterize 1) the difference in the diffusion gradient of cellular oxygen delivery and 2) the presence of diffusion limitation physiology in hypoxic-ischemic brain injury patients with brain hypoxia, as defined by parenchymal brain tissue oxygen tension less than 20 mm Hg versus normoxia (brain tissue oxygen tension > 20 mm Hg). Design: Post hoc subanalysis of a prospective study in hypoxic-ischemic brain injury patients dichotomized into those with brain hypoxia versus normoxia. Setting: Quaternary ICU. Patients: Fourteen adult hypoxic-ischemic brain injury patients after cardiac arrest. Interventions: Patients underwent monitoring with brain oxygen tension, intracranial pressure, cerebral perfusion pressure, mean arterial pressure, and jugular venous bulb oxygen saturation. Data were recorded in real time at 300Hz into the ICM+ monitoring software (Cambridge University Enterprises, Cambridge, United Kingdom). Simultaneous arterial and jugular venous bulb blood gas samples were recorded prospectively. Measurements and Main Results: Both the normoxia and hypoxia groups consisted of seven patients. In the normoxia group, the mean brain tissue oxygen tension, jugular venous bulb oxygen tension, and cerebral perfusion pressure were 29 mm Hg (SD, 9), 45 mm Hg (SD, 9), and 80 mm Hg (SD, 7), respectively. In the hypoxia group, the mean brain tissue oxygen tension, jugular venous bulb oxygen to brain tissue oxygen tension gradient, and cerebral perfusion pressure were 14 mm Hg (SD, 4), 53 mm Hg (SD, 8), and 72 mm Hg (SD, 6), respectively. There were significant differences in the jugular venous bulb oxygen tension–brain oxygen tension gradient (16 mm Hg [sd, 6] vs 39 mm Hg SD, 11]; p < 0.001) and in the relationship of jugular venous bulb oxygen tension–brain oxygen tension gradient to cerebral perfusion pressure ( p = 0.004) when comparing normoxia to hypoxia. Each 1 mm Hg increase in cerebral perfusion pressure led to a decrease in the jugular venous bulb oxygen tension–brain oxygen tension gradient by 0.36 mm Hg (95% CI, –0.54 to 0.18; p < 0.001) in the normoxia group, but no such relation was demonstrable in the hypoxia group. Conclusions: In hypoxic-ischemic brain injury patients with brain hypoxia, there is an elevation in the jugular venous bulb oxygen tension–brain oxygen tension gradient, which is not modulated by changes in cerebral perfusion pressure. Abstract : Supplemental Digital Content is available in the text.